The Effect of Using Grammarly Application to Improve Students' Writing Skill at Tenth Grade of SMAN 14 Kota Tangerang in Academic Year 2020/2021 - Isnaniah, Isnaniah; Maulida, Anna (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2022)
The research aimed to know whether there is a significant effect of using the Grammarly application to improve students’ writing skill at tenth grade of SMAN 14 Kota Tangerang. This research is quantitative method, 64 students of X MIPA 1 and X MIPA 4, as the sample which taken nonrandom by using quasi-experimental research non-equivalent control group design. Students test was used by the researcher to collect the data through pre-test and post-test. The result of this research was statistical calculation by One-Sample Kolmogorov-Smirnov test, it is known the asymptotic significances of the pre-test and post-test in experimental class data is 0.000<0.05. It can be concluded that Ha is accepted and Ho is rejected. It means there is significant difference using the Grammarly application to improve students’ writing skill. Therefore, it can be concluded that there is positive effect using theGrammarly application to improve students’ writing skills in the tenth grade of SMAN 14 Kota Tangerang in the academic year 2020/2021.